The Dark Side of Acid Suppression: Exploring Mood Changes in Omeprazole treated Mice - Safa Elbadri,; Khadija Mohammed,; Arig Mesallati, (AlQalam Journal of Medical and Applied Sciences, 2024)
Depression is considered as one of the most common major health obstacles in the communities, according to World Health Organization (WHO) about 3.8% of population are suffering from depression. The prevalence of depression in Libya is 23.68%, excluding other mental and psychiatric disorders. Few studies and experiments bay attention about the significance of pharmacological cause of depression. The researchers have turned their focus to the association between Proton pump inhibitors (PPIs) and depression and suicidal attempts, which are considered as one of the most common prescribed drugs and can be sold without prescriptions in some nations. The aim of Study is assessment omeprazole's possible depressive-like effects on experimental animals. Behavioral tests: the tail suspension test (TST), forced swim test (FST), and sucrose preference test (SPT) were used to evaluate different behavioral changes in male Swiss albino mice after they were given omeprazole (40 mg/kg) for 15 days. According to our findings, the omeprazole (40 mg/kg) had a significant effect (p < 0.01) on the tail suspension test and the forced swim test, and both tests had longer immobility times. An indicator of anhedonia, sucrose preference, was dramatically reduced by omeprazole (p value < 0.01). A one-way ANOVA of the body weight data showed that it was not significant (p > 0.05). Concerns about the long-term use of omeprazole are raised by the depressive-like effects seen in this study, especially in patients who may be taking the drug for longer periods of time. However, the supporting evidence remains limited, necessitating further research to comprehensively understand the implications of these drugs on mental health. يُعتبر الاكتئاب أحد أكثر العقبات الصحية شيوعًا في المجتمعات، ووفقًا لمنظمة الصحة العالمية يعاني حوالي 3.8٪ من السكان من الاكتئاب. وتبلغ نسبة انتشار الاكتئاب في ليبيا 23.68٪، مع استثناء الاضطرابات العقلية والنفسية الأخرى. القليل من الدراسات والتجارب ركزت على الأهمية المحتملة للأسباب الدوائية للاكتئاب. وقد وجه الباحثون اهتمامهم نحو العلاقة بين مثبطات مضخات البروتون والاكتئاب ومحاولات الانتحار، حيث تُعتبر هذه الأدوية من بين الأكثر شيوعًا في الوصفات الطبية، كما يمكن بيعها بدون وصفة طبية في بعض البلدان. يهدف البحث إلى تقييم التأثيرات المحتملة المشابهة للاكتئاب الناتجة عن استخدام دواء الأوميبرازول على الحيوانات التجريبية. تم استخدام اختبارات سلوكية: اختبار التعليق الذيل، اختبار السباحة القسرية، واختبار تفضيل السكروز لتقييم التغيرات السلوكية المختلفة لدى ذكور الفئران السويسرية البيضاء بعد إعطائها جرعة من الأوميبرازول (40 مجم/كجم) لمدة 15 يومًا.تشير النتائج إلى أن الأوميبرازول (40 مجم/كجم) كان له تأثير ملحوظ (p < 0.01) على اختبار التعليق الذيل واختبار السباحة القسرية، حيث أظهرت كلا الاختبارين زيادة في أوقات الجمود. كما أن تفضيل السكروز، وهو مؤشر على فقدان الاستمتاع (أنهدونيا)، انخفض بشكل كبير بسبب تأثير الأوميبرازول (p < 0.01).أظهرت نتائج تحليل التباين الأحادي لبيانات وزن الجسم أنها لم تكن ذات دلالة إحصائية (p > 0.05). تثير هذه الدراسة القلق بشأن الاستخدام طويل الأمد للأوميبرازول، نظرًا للتأثيرات المشابهة للاكتئاب التي لوحظت، خاصة لدى المرضى الذين قد يتناولون الدواء لفترات طويلة. ومع ذلك، لا تزال الأدلة الداعمة محدودة، مما يستدعي إجراء المزيد من الأبحاث لفهم التأثيرات المحتملة لهذه الأدوية على الصحة العقلية بشكل شامل